2008
DOI: 10.3354/meps07543
|View full text |Cite
|
Sign up to set email alerts
|

Ocean iron fertilization and international law

Abstract: Intentional ocean fertilization and the commercial sale of associated carbon offsets raise a number of issues in international law. On the one hand, states are obliged to adopt adaptation and mitigation measures to prevent dangerous climate change. On the other hand, international law obliges states to protect and preserve the marine environment and to act in a precautionary manner in the face of scientific uncertainty. In this article, we examine the application of the international Law of the Sea to ocean fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…To our knowledge, except for a few speculations (Wayman 2008;Freestone and Rayfuse 2008) no scientific study has addressed this issue. In a recently released report on ocean acidification, "Monaco Declaration" (Monaco Declaration 2009), it states that "Mitigation strategies that aim to transfer CO 2 to the ocean, for example by direct deep-sea disposal of CO 2 or by fertilising the ocean to stimulate biological productivity, would enhance ocean acidification in some areas while reducing it in others".…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, except for a few speculations (Wayman 2008;Freestone and Rayfuse 2008) no scientific study has addressed this issue. In a recently released report on ocean acidification, "Monaco Declaration" (Monaco Declaration 2009), it states that "Mitigation strategies that aim to transfer CO 2 to the ocean, for example by direct deep-sea disposal of CO 2 or by fertilising the ocean to stimulate biological productivity, would enhance ocean acidification in some areas while reducing it in others".…”
Section: Introductionmentioning
confidence: 86%
“…There are a few speculations in the literature (Wayman 2008;Freestone and Rayfuse 2008) that ocean iron fertilization could help to mitigate anthropogenic ocean acidification, a process referring to the increase in ocean acidity as a result of the ocean's absorption of anthropogenic CO 2 (Caldeira and Wickett 2003). Ocean acidification would affect marine organisms and ecosystems in a variety of ways (Raven et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…It is suggested that ocean fertilization should be regulated to ensure precautions are taken in this practice (Orbach, 2008). Inconsistency of current international laws in this field is also recognized as a challenge (Freestone and Rayfuse, 2008).…”
Section: Carbon Dioxide (Co 2 ) Fixation By Microalgaementioning
confidence: 99%
“…The reference to "global rules and standards" contained in this norm is generally understood as a reference to the Convention on the Even if iron filings introduced into the marine environment were not classified as "wastes", they would still be classified as "other matter". Since they will remain in the ocean, "disposal" appears to be occurring Freestone and Rayfuse, 2008). However, this alone does not lead to the conclusion that OIF constitutes "dumping".…”
Section: Relevant International Agreementsmentioning
confidence: 99%